2021
DOI: 10.1093/jme/tjab183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Volatile Plant Compounds of Psidium galapageium (Myrtales: Myrtaceae) as Repellents Against Invasive Parasitic Diptera in the Galapagos Islands

Abstract: Plant-based repellents represent a safe, economic, and viable alternative to managing invasive insects that threaten native fauna. Observations of self-medication in animals can provide important cues to the medicinal properties of plants. A recent study in the Galapagos Islands found that Darwin’s finches apply the leaves of Psidium galapageium (Hooker 1847) to their feathers, extracts of which were repellent to mosquitoes and the parasitic fly Philornis downsi (Dodge & Aitkens 1968; Diptera: Muscidae). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Studies have shown that birds use natural and synthetic material to reduce parasite load (Clayton & Wolfe 1993;De Roode et al 2013). In the Galápagos, Cimadom et al (2016) observed that Darwin's nches treat their feathers with the leaves of the endemic Galápagos guava (Psidium galapageium), which, in the lab, inhibits the growth of vampire y larvae and repels adults (Martina et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that birds use natural and synthetic material to reduce parasite load (Clayton & Wolfe 1993;De Roode et al 2013). In the Galápagos, Cimadom et al (2016) observed that Darwin's nches treat their feathers with the leaves of the endemic Galápagos guava (Psidium galapageium), which, in the lab, inhibits the growth of vampire y larvae and repels adults (Martina et al 2022).…”
Section: Introductionmentioning
confidence: 99%